2009
DOI: 10.1111/j.1442-200x.2009.02871.x
|View full text |Cite
|
Sign up to set email alerts
|

Late‐onset, unusual neurological symptoms in children with mycoplasma infection

Abstract: Mycoplasma infections involve pulmonary and various extrapulmonary organs, but the importance to each organ of direct invasion and cytotoxicity has not yet been determined. Immune responses to Mycoplasma pneumoniae infection result in the production of a large number of autoantibodies against lung, liver, erythrocytes, heart, and brain, 1 possibly due to crossreactivity between M. pneumoniae and human tissue antigens. 2 Production of these autoantibodies may well be responsible for the manifestations of mycopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In the CEP study, eighty percent of 84 patients were positive for M. pneumoniae by serology alone [11], and CSF -PCR for M. pneumoniae was rarely positive (2%) [11], The presence of IgM antibodies specific to M. pneumoniae are a reliable determinant of acute infection since they typically appear within 1 wk of the initial infection [39]. It is widely held that immunological sequelae of M. pneumoniae infection account for some of the neurologi-cal complications [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], which supports the use of corticosteroids in treatment. There are both identified case series and case reports of use of corticosteroids in patients of Mycoplasma pneumonia CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CEP study, eighty percent of 84 patients were positive for M. pneumoniae by serology alone [11], and CSF -PCR for M. pneumoniae was rarely positive (2%) [11], The presence of IgM antibodies specific to M. pneumoniae are a reliable determinant of acute infection since they typically appear within 1 wk of the initial infection [39]. It is widely held that immunological sequelae of M. pneumoniae infection account for some of the neurologi-cal complications [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], which supports the use of corticosteroids in treatment. There are both identified case series and case reports of use of corticosteroids in patients of Mycoplasma pneumonia CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Since autoimmunity has been suggested as a mechanism of CNS involvement; this has led clinicians to consider the use of corticosteroids for these patients. Its use has been described in case reports and case series and has shown good results [20,[24][25][26][27][28][29][30][31][32][33][34][35]. We report here a severe case of mycoplasma-associated encephalitis that had full recovery with the use of high dose corticosteroids.…”
Section: Introductionmentioning
confidence: 92%
“…Although the positive PCR in CSF are very useful in cases, are insufficient .We prefer to test CSF from both serological and PCR aspect in highly suspicious cases (18). Anti-microbial or immune modulating therapies (Corticosteroids, intravenous immunoglobulin) had possible benefits in treating such complications (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…M. pneumonia (DNA-PCR) was the most common agent implicated in unexplained encephalitis in the California Encephalitis Project (14). Many studies recommend various anti-microbial or immune modulating therapies in treating CNS manifestations of M. pneumonia (15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, both the infectious agent and the presentation of the movement disorder show a wide variability, depending on the geographical location. For example, studies conducted in India have shown a higher prevalence of rheumatic fever and tetanus [57] compared to cases of Mycoplasma pneumoniae infection leading to motor abnormalities in both the USA [28] and Japan [58].…”
Section: Post-infectious Encephalitismentioning
confidence: 99%